Sérgio Capparelli e a poesia digital para crianças - Capelesso, Odete Teresa Sutili (2010)
This study is about the advantages of the languages and production and reception ways of the lyric text destined for children, when poetical art and technology are united. Behind these productions, those from Sérgio Capparelli, are chosen as a study object, founded at the websites Zoom na Poesia, Ciber&Poema and Terrarium Kid. To investigate, therefore, the Capparelli s digital s poetry, destined to children and their implications resulting from the hybrid process of the languages and the constitution of a new text paradigm, reading and reader, appoints the focus of this job. Among the examined questions, it is possible to highlight the procedures used by the writer in the construction of a childish poetics, the specification of digital poems and the interactivity as a powerful machine of the interaction between the text and the reader. It is used the analytical-descriptive method to the investigation and discussion of the main characteristics of the poems, aiming at their specifications, considering the child-receiver and the digital mean on which the productions are inserted. It is used, this way, to the contribution of Ziberman, Bordini, Fialho Ponde, Jesualdo Pound, Colomer and Coelho, to think about the production and the reception of the printed literary text destined for the child, emphasizing the case of the poetry. Iser supports the theoretical formulations of the emancipated nature of the reading, resulting of the reader-text interaction. Chartier, Santaella and Beiguelman establish the discussions about the new reader and the new way of reading, which are configured with the digital text. Lévy, Jensen, Manovich, Kerckhove, Plazza, Primo, Machado and Silva orientate the reflection trying to understand the changes in the center line of the artistic text reception mediated by technical interfaces, highlighting the problems about the hypertext, interactivity, virtual issues as concepts which maintain the receiver participation in the digital art work in the cyberculture context. Finally, Santos, Capparelli, Góes and Assumpção support the reflections about the childish poetry for a new reader. Based on the used analysis, it becomes evidenced that the main importance of reading in this new text format, the lyric hypertext, concerns about the possibilities already latent in the printed poem, which highlight its reading in the literary perspective